Apolipoprotein D-mediated preservation of lysosomal function promotes cell survival and delays motor impairment in Niemann-Pick type A disease - Raquel Pascua-Maestro; Miriam Corraliza-Gomez; Cristian Fadrique-Rojo; Maria D. Ledesma; Edward H. Schuchman; Diego Sanchez; Maria D. Ganfornina (Neurobiology of Disease, 2020)
Lysosomal Storage Diseases (LSD) are genetic diseases causing systemic and nervous system dysfunction. The glia-derived lipid binding protein Apolipoprotein D (ApoD) is required for lysosomal functional integrity in glial and neuronal cells, ensuring cell survival upon oxidative stress or injury. Here we test whether ApoD counteracts the pathogenic consequences of a LSD, Niemann Pick-type-A disease (NPA), where mutations in the acid sphingomyelinase gene result in sphingomyelin accumulation, lysosomal permeabilization and early-onset neurodegeneration. We performed a multivariable analysis of behavioral, cellular and molecular outputs in 12 and 24 week-old male and female NPA model mice, combined with ApoD loss-of-function mutation. Lack of ApoD in NPA mice accelerates cerebellar-dependent motor deficits, enhancing loss of Purkinje neurons. We studied ApoD expression in brain sections from a NPA patient and age-matched control, and the functional consequences of ApoD supplementation in primary human fibroblasts from two independent NPA patients and two control subjects. Cell viability, lipid peroxidation, and lysosomal functional integrity (pH, Cathepsin B activity, Galectin-3 exclusion) were examined. ApoD is endogenously overexpressed in NPA patients and NPA mouse brains and targeted to lysosomes of NPA patient cells, including Purkinje neurons and cultured fibroblasts. The accelerated lysosomal targeting of ApoD by oxidative stress is hindered in NPA fibroblasts, contributing to NPA lysosomes vulnerability. Exogenously added ApoD reduces NPA-prompted lysosomal permeabilization and alkalinization, reverts lipid peroxides accumulation, and significantly increases NPA cell survival. ApoD administered simultaneously to sphingomyelin overload results in complete rescue of cell survival. Our results reveal that ApoD protection of lysosomal integrity counteracts NPA pathology. ApoD supplementation could significantly delay not only the progression of NPA disease, but also of other LSDs through its beneficial effects in lysosomal functional maintenance.